2010
DOI: 10.1159/000283560
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Neuroendocrine Response to Hypoglycemic Stress in Patients with Panic Disorder

Abstract: Background/Aims: There is a lack of information on the effects of metabolic stress exposure on hormone release in patients with panic disorder. The aim of this study was to test the hypothesis that neuroendocrine activation during hypoglycemic stress is altered in panic disorder patients compared to healthy subjects. Methods: Hormone responses to an intravenous bolus of insulin (0.1 IU/kg) were evaluated in both fully remitted, medication-free panic disorder patients and healthy controls (n = 9/group). Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…However, not only exaggerated but also inadequate HPA activation in response to demanding stimuli may have negative consequences. Consistently, patients with an anxiety disorder showed attenuated response to hypoglycemia compared to healthy controls [ 16 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, not only exaggerated but also inadequate HPA activation in response to demanding stimuli may have negative consequences. Consistently, patients with an anxiety disorder showed attenuated response to hypoglycemia compared to healthy controls [ 16 ].…”
Section: Discussionmentioning
confidence: 95%
“…Lower plasma cortisol levels are found in several stress-associated neuropsychiatric disorders, e.g. posttraumatic stress disorder, panic disorders and chronic pain and fatigue syndromes [36,37,38]. This resembles the findings in our study, with more complaints of pain and fatigue being reported by patients receiving the lower dose of HC, an intriguing finding which points to a direct role for HC rather than to other hormones of the hypothalamic-pituitary-adrenal axis because feedback regulation is absent in our patients due to their pituitary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased trait anxiety as a personal characteristic is likely to have a sustained influence on the behavior and strategies of stress coping. Since patients with certain anxiety disorders also exhibit similar patterns of neuroendocrine changes during stress [4,5], it may be suggested that the reduced hormonal and cardiovascular response is inadequate. The present findings demonstrate that even an acute increase in state anxiety is enough to modulate physiological reactivity under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, reduced activation of the hypothalamic-pituitary-adrenocortical axis associated with high trait anxiety has been confirmed in animal studies [3]. Moreover, this phenomenon has been observed in patients with panic disorder [4,5]. …”
Section: Introductionmentioning
confidence: 89%